Improvements in carbon fibre reinforced composites by inkjet printing of thermoplastic polymer patterns. Issue 1 (5th November 2013) - Zhang, Yi; Stringer, Jonathan; Grainger, Richard; Smith, Patrick J.; Hodzic, Alma
Abstract A thermoplastic polymer solution was inkjet printed in a pre‐defined hexagonal pattern onto carbon fibre reinforced epoxy resin (CFRP), leading to a significant increase in strength, stiffness and toughness of the final aerospace grade compo‐site system. The approach consisted of depositing low‐viscosity polymer microdroplets having chemically and me‐chanically comparable properties to epoxy polymer, onto CFRP before curing and solidification. The microdroplets remained arrested between composite plies without direct contact with the neighbouring microdroplets ensuring preservation of the structural integrity of the new composite system after curing. The key to achieving this synergistic effect was in appropriately selected additive materials; however, the novel aspects also included the method itself, which enabled an accurate crack arrest mechanism. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Inkjet printing of thermoplastic droplets in a hexagonal pattern on resin pre‐impregnated carbon fibre, showing increased mechanical properties. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)